Growth Accounting and Growth Processes - Aziz, Jahangir (IMF Working Papers; Working Paper ;, 1996)
The standard growth accounting framework, which weights various inputs by their factor shares to measure their contributions to output growth, is known to underestimate the contribution of inputs in the presence of externalities and increasing returns. This paper develops a model in which, in the absence of such departures from the standard neoclassical framework, growth can occur through either embodied technological progress or firms replication of existing technology. The standard growth accounting framework fails to distinguish between these contrasting development processes. This failure thus reveals another limitation to the use of growth accounting in identifying the processes of economic developments.